Paternity patterns in a long-term resident bottlenose dolphin community - Debbie Duffield; Randall Wells (Frontiers in Marine Science, 2023)
Genetic analyses, initiated in 1984, have played a major role in our understanding of the structure and social relationships of the long-term resident community of common bottlenose dolphins ( Tursiops truncatus ) in Sarasota Bay, Florida (SBDC). One component of our ongoing study of the community’s social system involves using blood samples from periodic catch-and-release sampling for life history and health assessment studies, as well as skin from biopsy dart sampling studies and strandings, to investigate paternity and mating strategies in this community. These analyses, covering a span of four generations of calves, were originally based on chromosomes and protein electrophoresis, but with the advent of microsatellite DNA technology, the latter has become our analysis of choice. We have performed paternity analyses on 204 known mother-calf pairs. For 151 of the calves (74%), sires were identified within the SBDC, but for the remaining 26% of the calves all sampled males associated with the community were excluded and it is likely that a substantial contribution of paternity to the SBDC comes from outside the community. Of the SBDC males, only 52 males of the more than 200 potential sires were sires. The age of sires at time of conception of a calf ranged from 10 to 43 years, averaging 24 years old. These males have sired 1-7 calves during a documented period of reproductive tenure of as much as 24 years (average = 21.4 years). Four males have sired 6-7 calves each, these males siring calves in the community for more than 20 years. Another 19 males have each sired 3-5 calves and the remaining 30 males were identified as sires of 1-2 calves. Paired males sired 75% of the calves while 25% of the calves were sired by unpaired males. Females with multiple offspring generally had multiple sires for these offspring. These paternity analyses support the hypothesis that a major avenue of gene flow in the SBDC is through the males given their greater ranges, with occasional exchange via visits from males from other areas, as well as the occasional brief movements of females from outside the community range into the community.

Reemergence of Guadalupe fur seals in the U.S. Pacific Northwest: The epidemiology of stranding events during 2005–2016 - Erin D'Agnese; Dyanna Lambourn; James Rice; Debbie Duffield; Jessica Huggins; Terry Spraker; Stephen Raverty; Tetiana Kuzmina; Michael E. Grigg; Kristin Wilkinson; Steven Jeffries; Woutrina Smith (Marine Mammal Science, 2020)
Guadalupe fur seals (GFS), Arctocephalus philippii townsendi , an U.S. Endangered Species Act threatened pinniped, have recently reappeared in their historic range along the western seaboard of the continental United States. Starting 2005 through 2016, 169 GFSs stranded in Washington and Oregon, involving two designated unusual mortality events. The circumstances surrounding GFS strandings, mortality, and their increased presence in Oregon and Washington were analyzed during this study. Detailed necropsies, histopathology ( n = 93), and epidemiological analysis found three main causes of death (COD): emaciation (44%), trauma (29%), and infectious disease (19%) and the factors associated with overall strandings and emaciation. Trauma included many cases found associated with fisheries interactions and clustered near the mouth of the Columbia River, where high levels of commercial fishing occur. The most common pathogens found associated with disease were Toxoplasma gondii , Sarcocystis neurona , and gastrointestinal helminths. Seasonality and upwelling were associated with higher stranding numbers regardless of COD. Seasonal migration into the region, coinciding with postweaning, suggests young GFSs are in search of prey and habitat resources. Reemergence of GFSs is likely due to conservation efforts, which have been critical for species recovery in the region. Continued monitoring is needed as this vulnerable species continues to rebound.

Maternal characteristics and the production and recruitment of sons in the eastern kingbird (Tyrannus tyrannus) - Amy C. Dolan; Michael T. Murphy; Lucas J. Redmond; Debbie Duffield (Behavioral Ecology and Sociobiology, 2009)